2010
DOI: 10.1007/s00264-010-1151-0
|View full text |Cite
|
Sign up to set email alerts
|

Clavicle fractures: a comparison of five classification systems and their relationship to treatment outcomes

Abstract: We compared five classification systems for clavicle fractures. The aim of this study was to evaluate the prognostic value of each system. Over a two-year period we reviewed all new radiographs of the shoulder region and identified 487 clavicle fractures. Each radiograph was classified using five classification systems. We reviewed all subsequent X-rays and clinical records until the patient was discharged. We assessed each classification system's prognostic value in predicting delayed/non-union. Our data show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 27 publications
1
49
0
3
Order By: Relevance
“…The Robinson classification has been stated to provide the most reliable prognostic information compared to the other classification methods for midshaft clavicular fractures [12,5]. We found no other studies on the reliability of classification systems for clavicular fractures to compare our data with.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations
“…The Robinson classification has been stated to provide the most reliable prognostic information compared to the other classification methods for midshaft clavicular fractures [12,5]. We found no other studies on the reliability of classification systems for clavicular fractures to compare our data with.…”
Section: Discussionsupporting
confidence: 41%
“…The current study shows that the extent of comminution, as displayed in simple or wedge comminuted (2B1) and isolated or segmental comminuted fractures (2B2), is difficult to classify on both AP and 30-degree caudocephalad radiographs. The prognostic value of the Robinson classification as described by O'Neill et al [5] may therefore be overrated because there is a possibility that the clavicular fracture is wrongly classified. In contrast to our study, Jones et al [9] found a moderate to strong inter-and intra-observer agreement for displacement and comminution on similar radiographs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1) Most clavicle fractures involve the midshaft, which is the thinnest part with the least soft tissue, and more than half of midshaft fractures are displaced. 2,3) Due to the reported unsatisfactory results after nonoperative treatment, operative fixation has been the recent treatment trend for the displaced midshaft clavicle fracture.…”
Section: Introductionmentioning
confidence: 99%